Effects of the difference foot strike pattern on the plantar pressure during uphill and downhill running - Horiguchi, Yoshiki; Noro, Hiroaki; Hata, Keiichiro; Yamazaki, Yohei; Kubota, Atsushi; Yanagiya, Toshio (Frontiers in Sports and Active Living, 2025)
The purpose of this study was to clarify the effects of foot strike patterns on plantar pressure distribution during uphill, level, and downhill running. Eleven participants performed six randomized trials on a treadmill running at 3.33 m/s, combining two foot strike patterns, rearfoot strike and forefoot strike with three slope conditions of −6°, 0° and +6°. Plantar pressure data were collected using a pressure measurement insole. Peak pressure, peak force, time to peak, and loading rate were calculated for the heel, midfoot, and forefoot regions. As a result, at the heel region, peak pressure in rearfoot strike increased by approximately 32.1% during downhill running and decreased by approximately 24.3% during uphill running compared to level running. At the forefoot region, regardless of the foot strike pattern, peak pressure decreased by approximately 6.8% during downhill running compared to level running, but no significant differences were observed between uphill and level running. These results provide a useful basis for the development of injury prevention and performance improvement during slope running.